INTEGRATION OF RESTORATIVE JUSTICE IN MEDICAL DISPUTE RESOLUTION AS A REFORM TO THE INDONESIAN CRIMINAL LAW SYSTEM - Mhd Azhali Siregar; Rahul Ardian Fikri; Ayuda Silitonga (PT. Sinergi Legal Publisher, 2024)
Medical dispute resolution in Indonesia often presents a dilemma between the criminal law aspect and the need for a more humane approach. The integration of Restorative justice in handling medical disputes offers a new paradigm that prioritizes the restoration of relationships between the parties involved, rather than focusing only on punishment. This approach is in line with the principle of restorative justice that places victims, perpetrators, and communities in a collaborative and dialogue-based resolution process. This study aims to explore the concept of integrating Restorative justice into the Indonesian criminal law system as a step towards legal reform that is more relevant and contextual to the needs of modern society. With normative juridical methods and analytical approaches, the results of the study show that the application of Restorative justice in medical disputes can encourage the creation of more inclusive justice, reduce conflict levels, and increase public trust in the legal system. Therefore, regulatory reform that accommodates Restorative justice in resolving medical disputes is an urgent need to realize a criminal law system that is more adaptive and responsive to social dynamics.